(3UMhI GdJhMjO (B:s (3OQGSI aj CReI GdNWGH GdSjGSj GdESdGej (B/s - (3GdYHO GdcQje, eMeOs ((3HjQhJ (B- (3dHfGf (B:s (3GdTHcI GdYQHjI ddCHMGK hGdfTQ ,s, 2013)
(3jYjO gPG GdcJGH JQJjH MjGI GdEfSGf GdeSde ef LOjO, dJLYdg UGdMG aj faSg djYHO QHg dG TQjc dg HdG bjhO, gj UMhI hgj JLOjO aj GdNWGH Gdabgj hGdYbOj hGdSjGSj, HYO UMhI LRFjI cQSJ eaGgje GdJaQO hde jcJed fehgG hde jSJaO ef MQGcgG hehLgGJgG EdG GdJZdH hGdJaQO aEPG HgG JRjO ef VQGhI GdLhQ hJNda GdEfSGf(B. s
Keywords: (3GdESdGe hGdSjGSIs; (3JMdjd GdNWGHs